Why we Should Rethink Our Approach to Embodiment and Presence - Forster, Pierre-Pascal; Karimpur, Harun; Fiehler, Katja (Frontiers in Virtual Reality, 2022)
When interacting with objects in the environment, it feels natural to have a body which moves in accordance to our intentions. Virtual reality (VR) provides a tool to present users with an alternative virtual body and environment. In VR, humans embody the presented virtual body and feel present in the virtual environment. Thus, embodiment and presence frequently co-occur and share some communalities. Nevertheless, both processes have been hardly considered together. Here, we review the current literature on embodiment and presence and present a new conceptual framework, the Implied Body Framework (IBF), which unifies both processes into one single construct. The IBF can be used to generate new hypotheses to further improve the theoretical conceptualisation of embodiment and presence and thus, facilitate its transfer into application.